Creating an Optimal 3D Printed Model for Temporal Bone Dissection Training. (July 2017) - Takahashi, Kuniyuki; Morita, Yuka; Ohshima, Shinsuke; Izumi, Shuji; Kubota, Yamato; Yamamoto, Yutaka; Takahashi, Sugata; Horii, Arata
Objective: Making a 3-dimensional (3D) temporal bone model is simple using a plaster powder bed and an inkjet printer. However, it is difficult to reproduce air-containing spaces and precise middle ear structures. The objective of this study was to overcome these problems and create a temporal bone model that would be useful both as a training tool and for preoperative simulation. Methods: Drainage holes were made to remove excess materials from air-containing spaces, ossicle ligaments were manually changed to bony structures, and small and/or soft tissue structures were colored differently while designing the 3D models. The outcomes were evaluated by 3 procedures: macroscopic and endoscopic inspection of the model, comparison of computed tomography (CT) images of the model to the original CT, and assessment of tactile sensation and reproducibility by 20 surgeons performing surgery on the model. Results: Macroscopic and endoscopic inspection, CT images, and assessment by surgeons were in agreement in terms of reproducibility of model structures. Most structures could be reproduced, but the stapes, tympanic sinus, and mastoid air cells were unsatisfactory. Perioperative tactile sensation of the model was excellent. Conclusions: Although this model still does not embody perfect reproducibility, it proved sufficiently practical for use in surgical training.